Oral history an introduction for students - Hoopes, James 1944- (Chapel Hill University of North Carolina Press, 1979)
A "how to" book adapting some of the best methods of group oral history projects to the needs of individual students.
History and oral history -- Oral history for the student -- Personality -- Culture -- Society -- Arranging the interview -- Preparing for the interview -- Conducting the interview -- Asking questions -- After the interview -- Writing the paper -- Matters legal and ethical -- Oral
Php 250.00
Includes bibliographical references (p. 151-155) and index.
Donated by Frank
Keywords: Oral history